Prediction of Antioxidant Capacity of Thai Vegetable Extracts by Infrared Spectroscopy - Trakul Prommajak (Science Faculty of Chiang Mai University, 2019)
The antioxidant capacity of extracts from 33 local Thai vegetables was determined by ABTS, DPPH, FRAP and FCRC assays. The extracts had a wide range of antioxidant activities and could be categorized into three groups: high, moderate and low antioxidant activities. The antioxidant activities of the four different assays were highly correlated (r > 0.98). Fourier transform infrared (FTIR) spectra and partial least square (PLS) regressions were used to predict the measured antioxidant capacities. The adjusted R2 was higher than 0.97 for prediction models and higher than 0.89 for cross-validation models, which could be applied on liquid extracts or freeze-dried extract. FTIR spectroscopy in combination with PLS regression successfully predicted the antioxidant capacity of several Thai vegetables.